Monkeypox Awareness Among the Syrian Doctors and Medical Students: A Cross Sectional Study - Swed, Sarya; Alibrahim, Hidar; Bohsas, Haidara; Amir Rais, Mohammed; Shoib, Sheikh; Khair Eldien Jabban, Yazan; Kazan, Lazaward; Hussain, Noor; Sawaf, Bisher (International Journal of Medical Students, 2023)
Background: World Health Organization (WHO) verified 780 cases of monkeypox across 27 countries between 13 May 2022 and 2 June 2022. The World Health Organization (WHO) classified the growing worldwide monkeypox epidemic a PHEIC on July 23; the bulk of confirmed cases have been found in European locations. The purpose of this research is to assess the level of awareness toward human monkeypox virus among the Syrian medical students, general practitioners (GPs), medical residents, and specialists. Methods: We performed a cross-sectional online survey in Syria between 2 may and 8 September, 2022 to assess medical students', general practitioners', residents', and specialists' knowledge about the monkeypox virus. The utilized tool was developed with input from the World Health Organization, the Centers for Disease Control and Prevention, and cross-sectional studies conducted in Indonesia. The survey has 53 questions divided into three groups: demographic information, work-related details, and monkeypox knowledge. The time-efficient and simple snowball method of sampling was used. Version 28.0 of SPSS was used to analyze the data. Results: A total of 1257 healthcare workers and medical students throughout all of Syria's governorates took part in the research. The percentage of responders who learned anything about monkeypox in medical school was just 6.2% (n = 78). As a whole, students scored 10.23 out of a possible 15, with 11 being the adequate level for knowledge. About half of the participants (n = 700) are familiar with the term "monkeypox." As well, half of the respondents (n = 663) just learned about monkeypox during the last few days, while almost half (n = 530) only learned about it within the past month. Almost participants didn't know adequately about monkeypox. The natural host and incubation time for monkeypox were correctly identified by just 2.7% of responders and 33.3% of the whole population, respectively. 1.8% of participants gave the right response when asked about the symptoms of monkeypox. Sixty percent of the study sample think the symptoms of monkeypox and smallpox are identical. The females had higher knowledge toward monkeypox (aOR = 1.5, 95% CI = 1.26-1.80, p<0.001) than males. Respondents who are specialist doctors had higher knowledge toward monkeypox (aOR = 2.96, 95% CI = 2.24-3.92, p<0.001) than others. Conclusion: Due to the critical lack of knowledge about monkeypox among Syrian clinicians and undergraduate medical students, urgent action to solve this local issue is required. Therefore, education and awareness regarding monkeypox vaccinations are of paramount importance. In order to improve the medical community's capacity to respond to human monkeypox cases and report them into a disease surveillance system, it is crucial that doctors have a better understanding of the illness.